Geospatial analysis of leptospirosis clusters and risk factors in two provinces of the Dominican Republic - Martin, Beatris Mario; Sartorius, Benn; Mayfield, Helen J.; Cadavid Restrepo, Angela M.; Kiani, Behzad; Then Paulino, Cecilia J.; Etienne, Marie Caroline; Skewes-Ramm, Ronald; de St. Aubin, Michael; Dumas, Devan; Garnier, Salomé; Duke, William; et al. (PLoS neglected tropical diseases, 2025)
Drivers of leptospirosis transmission can vary across regions, leading to spatial clustering of infections. This study aims to identify clusters of leptospirosis seroprevalence in the Dominican Republic (DR) and factors associated with high-risk areas. We analysed data from two provinces, Espaillat and San Pedro de Macoris (SPM), obtained on a national survey conducted in 2021 (n = 2,078). Samples were tested by microscopic agglutination testing (MAT) to detect leptospirosis antibodies. We used flexible spatial scan statistics to locate significant clusters for seropositive individuals (all serogroups combined) in each province and calculated risk ratios (RR) at the household and community level. Environmental and sociodemographic risk factors associated with clusters were assessed by logistic regression. One cluster was identified in each province. Participants living inside a cluster were more likely to live further from health facilities (OR 1.86, p < 0.001 and OR 4.41, p = 0.044 by motorized travel time in Espaillat and SPM, respectively). Cluster participants were also less likely to live in areas of higher population density (OR 0.76, p < 0.01 and OR 0.29, p < 0.001 in Espaillat and SPM, respectively) and in communities with higher gross domestic product (GDP) (OR 0.70, p < 0.001 and OR 0.42, p < 0.001 in Espaillat and SPM, respectively). Additional risk factors varied between Espaillat and SPM. Our findings confirm the clustered spatial pattern of leptospirosis and highlight that transmission drivers vary by province. While both provinces show higher transmission in impoverished areas, modifiable factors differ, requiring tailored public health interventions.